Novel autoantibodies to the β-cell surface epitopes of ZnT8 in patients progressing to type-1 diabetes. Issue 122 (August 2021) - Gu, Yong; Merriman, Chengfeng; Guo, Zheng; Jia, Xiaofan; Wenzlau, Janet; Li, Hua; Li, Huilin; Rewers, Marian; Yu, Liping; Fu, Dax
Abstract: Type 1 diabetes (T1D) is a chronic autoimmune disease characterized by autoimmune destruction of insulin-producing β-cells in pancreatic islets. Seroconversions to islet autoantibodies (IAbs) precede the disease onset by many years, but the role of humoral autoimmunity in the disease initiation and progression are unclear. In the present study, we identified a new IAb directed to the extracellular epitopes of ZnT8 (ZnT8ec) in newly diagnosed patients with T1D, and demonstrated immunofluorescence staining of the surface of human β-cells by autoantibodies to ZnT8ec (ZnT8ecA). With the assay specificity set on 99th percentile of 336 healthy controls, the ZnT8ecA positivity rate was 23.6% (74/313) in patients with T1D. Moreover, 30 children in a longitudinal follow up of clinical T1D development were selected for sequential expression of four major IAbs (IAA, GADA, IA-2A and ZnT8icA). Among them, 10 children were ZnT8ecA positive. Remarkably, ZnT8ecA was the earliest IAb to appear in all 10 children. The identification of ZnT8ec as a cell surface target of humoral autoimmunity in the earliest phase of IAb responses opens a new avenue of investigation into the role of IAbs in the development of β-cell autoimmunity. Highlights: Identification of a new islet cell autoantibody directed to the extracellular epitopes of ZnT8 (ZnT8ecA). Identification of ZnT8 as a molecular target of islet cell surface antibodies (ICSA). ZnT8ecA was the earliest autoantibody to appear in children followed longitudinally from birth to clinical type-1 diabetes.